Effectiveness and safety of nivolumab in patients with advanced melanoma: A multicenter, observational study. Issue 11 (19th February 2021) - Monestier, Sandrine; Dalle, Stéphane; Mortier, Laurent; Dutriaux, Caroline; Dalac‐Rat, Sophie; Meyer, Nicolas; Leccia, Marie Thérèse; Mansard, Sandrine; Montaudié, Henri; Saiag, Philippe; Combemale, Patrick; Guillot, Bernard; et al.
Abstract: This retrospective observational study aimed to determine the effectiveness, safety and patterns of the use of nivolumab in patients with advanced melanoma in real‐world clinical practice in France using data from a Temporary Authorization for Use Program (ATU). Data were collected from patients with unresectable or metastatic melanoma enrolled in a French national database (Réseau pour la Recherche et l'Investigation Clinique sur le Mélanome: Ric‐Mel) and treated with nivolumab during the ATU program (12 September 2014 to 31 August 2015). The primary objectives of the study were to evaluate the effect of patient characteristics on clinical response and overall survival (OS). Among 400 included patients (median age 66 years), the majority (83%) received nivolumab as second‐ or subsequent‐line therapy. The median durations of progression‐free survival and OS were 3.3 and 14.1 months, respectively, and 31.6% of patients achieved an objective response with a median duration of 20.1 months (range: 0‐34.7). The safety profile of nivolumab was manageable and consistent with those of previous clinical trials, with an incidence of grade 3‐5 adverse events of 13.8%. The safety and effectiveness of nivolumab in patients with advanced melanoma in real‐world clinical practice in France were in line with the data reported in the Phase 3 trials CheckMate 066 and 037 of nivolumab in this patient population. Abstract : What's new? Clinical trial data support the use of nivolumab in melanoma patients, and the drug received a Temporary Authorization for Use in France. Here, the authors present real‐world clinical data on the safety and efficacy of nivolumab collected from 400 patients with unresectable or metastatic melanoma. They found that the safety and efficacy in the real world context was consistent with the profile reported in phase 3 trials. The study also includes data from some sub‐populations that may have been underrepresented in the clinical trials.